Uji Beberapa Konsentrasi Ekstrak Akar Tuba (Derris elliptica Benth) untuk Mengendalikan Larva Kumbang Tanduk (Oryctes rhinoceros Linnaeus) pada Tanaman Kelapa Sawit: Test Some Concentrations of Tuba Root Extract (Derris elliptica Benth) to Control Horn Beetle Larvae (Oryctes rhinoceros Linnaeus) on Palm Oil Plant - Akbar, Muhammad Jalaludin; Rustam, Rusli (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2019)
Oryctes rhinoceros Linnaeus is one of the main pests of oil palm plants. The Oryctes rhinoceros control of being commonly used is synthetic insecticides. However, it is unwise useable to cause negative impacts on humans and the agricultural environment. Therefore, an alternative insecticide that is safer and environmentally friendly is needed, such as tuba root (Derris elliptica Benth.). The research was conducted in a Plant Pest laboratory, Faculty of Agriculture, University of Riau, Pekanbaru, from July to August 2018. This study aims to obtain an effective concentration of tuba root extract to control Oryctes rhinoceros larvae. The research was conducted experimentally using a Completely Randomized Design (CRD), which consists of five treatments and four replications. The treatment used is the concentration of tuba root extracts 0 g.l-1 of water, 25 g.l-1 of water, 50 g.l-1 of water, 75 g.l-1 of water and 100 g.l-1 of water. The result in them showing that the application of tuba root extract at a concentration of 75 g.l-1 was able to decrease O. rhinoceros larvae population with a total mortality of 82.5%. The lethal concentration to kill 50% of O. rhinoceros larvae population was 1.0% or equal to 10 g.l-1 of tuba root extract, while the lethal concentration to kill 95% of O. rhinoceros larvae population was 30.6% or equal to 306 g.l-1 tuba root extract.